Islamic Republic of Afghanistan : Second Review Under the Staff-Monitored Program-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses economic developments, outlooks, and risks in Afghanistan. The economy is in difficultly. Deepening uncertainty about the political transition following the 2014 presidential election, corruption and weak governance, and a weakening security environment have complicated the implementation of reforms, undermined confidence and economic activity, and contributed to increased emigration. The overall budget had a deficit in 2015 as a shortfall in grants more than offset higher-than-projected revenue and lower spending. The trade deficit remained large, but substantial inflows of foreign aid kept the current account in surplus. The financial sector remains fragile and plays a limited intermediation role.